2009
DOI: 10.1063/1.3274039
|View full text |Cite
|
Sign up to set email alerts
|

Influence of metal work function on the position of the Dirac point of graphene field-effect transistors

Abstract: Articles you may be interested inErratum: "Work function tuning and improved gate dielectric reliability with multilayer graphene as a gate electrode for metal oxide semiconductor field effect device applications" [Appl. Phys. Lett. 100, 233506 (2012)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 22 publications
0
15
0
Order By: Relevance
“…Moreover, it is assumed that the total voltage applied to the structure is less than 0.1 V; hence, the Fermilevel variation inside graphene is small. Due to the exclusion of the channel in the developed 1-D model, the asymmetry of conduction in the hole-and electron-dominated transport regimes in graphene-based field-effect transistors [17], [53], [54] is not modeled in this work.…”
Section: Metal-mlg Contact Structurementioning
confidence: 97%
See 1 more Smart Citation
“…Moreover, it is assumed that the total voltage applied to the structure is less than 0.1 V; hence, the Fermilevel variation inside graphene is small. Due to the exclusion of the channel in the developed 1-D model, the asymmetry of conduction in the hole-and electron-dominated transport regimes in graphene-based field-effect transistors [17], [53], [54] is not modeled in this work.…”
Section: Metal-mlg Contact Structurementioning
confidence: 97%
“…Furthermore, it has been shown that the metal contacts can alter the Fermi level and the density of states of graphene [40]- [44], [53], [54], [84], which leads to a change in the sheet resistivity of graphene under metal. Therefore, the contact resistance, which is determined by the slope of the I-V curve near the Fermi level, becomes strongly dependent on the type of metal.…”
Section: Metal-mlg Contact Structurementioning
confidence: 99%
“…Such an interface is characterized by weak bonding and charge transfer between the metal and graphene, which results in doping and a shift in the Fermi level from the Dirac point. For physisorption interfaces, the electronic structure of graphene remains essentially unperturbed, and hence, such contacts are ideal for probing the (magneto-) transport properties of pristine graphene [32,34,35]. "Chemisorption interface", on the other hand, is characterized by a strong chemical bond between graphene and metal (Co, Ni), with a concomitant modification of the electronic structure of pristine graphene, including elimination of the Dirac point, band gap opening and creation of metal-graphene hybrid localized states in the gap [30][31][32][33].…”
Section: Introductionmentioning
confidence: 99%
“…SnCl 4 ·5H 2 O was dissolved in CH 3 OH at a final concentration of 0.3 M and 2‐nitrobenzaldehyde (NBAL) was introduced as a photosensitive additive. The dissolved photosensitive solution was stirred at room temperature for 3 h. Graphene sheets were micromechanically cleaved from highly oriented pyrolytic graphite 12. Graphene in the mixed solution were dispersed by a sonicator 13.…”
Section: Methodsmentioning
confidence: 99%